Implementasi Sistem Komunikasi FM Pada Prototype Pendeteksi Dini Gempa - Charisma, Atik; Taryana, Een; Saputra, Dede Irawan; Misuari, Muhammad Burhannudin; Setiawan, Aldi; Dharmawan, Faisal (PROtek : Jurnal Ilmiah Teknik Elektro, 2020)
An earthquake is a vibration that occurs due to plates at the base of the earth rubbing against each other. An earthquake can have several impacts, namely material loss and loss of life and trauma for some people who feel it. This happens because people are not fast enough in getting information. Therefore we need an earthquake detection device that is relatively inexpensive. In this study designed a prototype for earthquake early detection using Frequency Modulation (FM) communication. The components of this system are Arduino Uno which functions as a microcontroller, SW-420 vibration sensor to detect vibrations, buzzer as the output of the SW-420 sensor in the form of sound and FM transmitter V2.0 which functions as a medium for transmitting radio frequency signals and sending sound from the buzzer . The level of vibration that indicates that an earthquake occurred namely 3-5 with a conversion of 5-10 SR. The system would have the ability to provide information in the form of sound received by a radio or FM receiver. The distance that can be emitted by the FM transmitter module V2.0 is 17.87 meter